Implementasi Pendidikan Inklusif di Madrasah Ibtidaiyah di Jawa Timur - Mochamad Syaifudin (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2021)
Many madrasas provide inclusive education, but have not yet received formal legal recognition from the government. So that the operational process is not implemented optimally. Therefore, this study attempts to analyze the implementation of inclusive education in East Java with the locus of MI Badrus Salam Surabaya, MINU Miftahul Ulum 91 Plinggisan Kraton Pasuruan and MI Terpadu Ar-Roihan Malang. The three were chosen because they have received operational permits to provide inclusive education since 2016. The type of research used was qualitative-descriptive with data collection methods, namely participant observation, in-depth interviews and documentation. From this research, it can be concluded that: firstly, the implementation of inclusive education at MI Badrus Salam Surabaya, MINU Miftahul Ulum 91 Plinggisan Kraton Pasuruan and MI Terpadu Ar-Roihan Malang is very good in terms of learning curriculum and creating an inclusive friendly environment. In providing GPK with ABK ratio, only MI Terpadu Ar-Roihan Malang is ideal compared to 2 other madrasas. Second, inclusive education is very meaningful for stakeholders in the three institutions. This is evidenced by the maximum support from madrasa heads, teachers, the government (in this case the Ministry of Religion), the business world and the industrial world in implementing inclusion programs in madrasas.